(untitled) (KYAMC Journal, 2017)
We report a case of a previously healthy woman, Mst. Borna Khatun, 25 years old, who developed puerperal sepsis with extensive lower abdominal necrotizing fasciitis after an uneventful home delivery. She presented to us with the complaints of lower abdominal pain, fever & foul smelling per vaginal discharge for 09 days with history of vaginal delivery by an untrained dai at home 13 days back. On general examination she was toxic, her temperature was 103F, and lower left half of abdomen was tender & rigid. On per vaginal examination there were foul smelling discharge & unhealthy lateral vaginal wall with laceration (small), with extensive debridement & daily dressing patient recovered & discharged. KYAMC Journal Vol. 5, No.-2, Jan 2015, Page 540-542